Rapid Innovation and Adaptation in Contraceptive Care Using Telemedicine: Evaluating Impact and Sustainability at Planned Parenthood of Illinois - Young, Danielle (My University, 2025)
Introduction: The COVID-19 pandemic necessitated swift, dramatic changes to the delivery of essential health care services. Numerous professional societies recommend telehealth care for contraceptive counseling and provision. We conducted a retrospective analysis of service delivery data from Planned Parenthood of Illinois (PPIL), a large reproductive health care provider with 17 health centers in Illinois, to understand if this model preserved access to contraceptive services during the COVID-19 emergency. Methodology: This retrospective analysis compared contraceptive service delivery data 12 months pre-pandemic (March 2019 - Feb 2020) to eight months post-pandemic onset (March 2020-October 2020). PPIL consolidated services to six health centers in late March 2020 and rapidly launched telehealth services in April 2020. Our primary outcome was time to appointment compared pre- and post-pandemic onset. We also compared access by race/ethnicity, age, and geography. Results: Although visit volume decreased (76% decline) and time to appointment increased post-pandemic onset (2.5-4 days higher), telehealth mitigated these changes and was used by patients across the entire catchment area. We observed no disparities among Black and Hispanic patients relative to white patients in the likelihood of using telehealth relative to in-person visits (OR 0.7, 95% CI 0.6–0.9 for both comparisons). Discussion: Telehealth can play an important role in preserving access to contraceptive services when the health care system is under strain and in increasing accessibility in underserved communities.
PUBLISHED
Keywords: health care services, contraception, telemedicine, COVID-19, quality